David Attwell, J.M. Coetzee, South Africa and the Politics of Writing, University of California Press, Berkeley, 1993, 147 pp. - Saavedra Casco, José Arturo (Estudios de Asia y África, 1995)
David Attwell, J.M. Coetzee, South Africa and the Politics of Writing, University of California Press, Berkeley, 1993, 147 pp.